Enterprise software architecture and design : entities, services and resources - Duggan, Dominic (Quantitative software engineering series, 2012)
This book fills a gap between high-level overview texts that are often too general and low-level detail oriented technical handbooks that lose sight the "big picture". This book discusses SOA from the low-level perspective of middleware, various XML-based technologies, and basic service design. It also examines broader implications of SOA, particularly where it intersects with business process management and process modeling. Concrete overviews will be provided of the methodologies in those fields, so that students will have a hands-on grasp of how they may be used in the context of SOA"